2004
DOI: 10.1016/j.febslet.2004.11.093
|View full text |Cite
|
Sign up to set email alerts
|

Heparin recovers AT1 receptor and its intracellular signal transduction in cultured vascular smooth muscle cells

Abstract: Although vascular smooth muscle cells (VSMCs) are widely used in cardiovascular research, their phenotypic change under various culture conditions is problematic to evaluate the experimental results obtained. The levels of angiotensin (Ang) type 1/2 (AT1/AT2) receptors as well as contractile and structural proteins are degraded through culture passages. The present study demonstrated that heparin recovered Ang receptors and differentiation markers, such as desmin, SM-22 and smooth muscle a-actin in VSMCs at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Deletion of Gq/11 in adult mouse VSMCs results in abolished vasoconstrictive responses, lower basal blood pressure, and reduced salt-induced hypertension (25). Importantly, we found that force generation of IP 3 R-deficient aortas was reduced in response to multiple vasoconstrictors, such as PE, U46619, 5-HT, and ET1, suggesting that IP 3 R-mediated Ca 2+ release plays an important role in regulating vascular contraction following activation of GPCR, which is consistent with previous studies using the IP 3 R blockers heparin, 2-APB, or Xestospongin (30)(31)(32)(33). Our results also suggested that both IP 3 R-dependent and IP 3 R-independent pathways could contribute to Gq/11-mediated regulation of vascular contraction, since deletion of Gq/11 has much more efficacy in reducing vasoconstrictive responses than deletion of IP 3 Rs.…”
Section: +supporting
confidence: 80%
“…Deletion of Gq/11 in adult mouse VSMCs results in abolished vasoconstrictive responses, lower basal blood pressure, and reduced salt-induced hypertension (25). Importantly, we found that force generation of IP 3 R-deficient aortas was reduced in response to multiple vasoconstrictors, such as PE, U46619, 5-HT, and ET1, suggesting that IP 3 R-mediated Ca 2+ release plays an important role in regulating vascular contraction following activation of GPCR, which is consistent with previous studies using the IP 3 R blockers heparin, 2-APB, or Xestospongin (30)(31)(32)(33). Our results also suggested that both IP 3 R-dependent and IP 3 R-independent pathways could contribute to Gq/11-mediated regulation of vascular contraction, since deletion of Gq/11 has much more efficacy in reducing vasoconstrictive responses than deletion of IP 3 Rs.…”
Section: +supporting
confidence: 80%
“…Real-time quantitative RT-PCR was also performed to examine the effect of salt depletion on MAK-V/Hunk and AT1 receptor mRNA expression in the mouse kidney, as described previously (13). Briefly, PCR was performed by incubating the RT product with the TaqMan Universal PCR Master Mix and designed TaqMan probe (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Vascular smooth muscle cells (VSMC) from the thoracic aorta of 4-week-old male Wistar rats were prepared by the explant method. 32 And human embryonic kidney (HEK) 293 cells were provided by ATCC (CRL-1573). These cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS), penicillin (100 U/ml), and streptomycin (100 U/ml) (all obtained from Invitrogen (ON, Canada)) at 371C in a humidified atmosphere of 95% air and 5% CO 2 .…”
Section: Materials and Methods Agents And Cell Culturementioning
confidence: 99%
“…Relative expression levels were expressed by a comparative threshold cycle (C T ) method as described previously. 32 Cell Growth Assay Cells (2.5 Â 10 4 cells/well) were plated on 96-well plates in DMEM with 10% FBS. After a 24-h incubation with 10% FBS, the cells were serum starved for 24 h, and then pretreated with CV11974 (4 Â 10 À5 mol/l) for 24 h and treated with various concentrations of AII (10 À6 , 10 À8 , 10 À10 , and 10 À12 mol/l) for 24 h. After a 2-day treatment, the net number of viable cells was determined using a water-soluble…”
Section: Western Blot Analysismentioning
confidence: 99%